BUGARIĆE (SRBOVAC) ACCORDING TO THE 1851 CENSUS (Heritage, 2025)
The village Bugariće, Srbоvac since 1913, is mentioned for the first time in sources in the Svetostefanska Hrisovulja of the monastery of Banjska, from Serbian King Milutin, and its development can be traced through a historical source. The village is recorded by Turkish censuses during the entire period of rule, as well as by various travel writers. In recent years, the first modern census of the male population, conducted by the Ottoman administration throughout its territory, has become available to the professional public. The area in which the village Bugariće is located, as well as the entire nahija Mitrovica in the Novi Pazar kadiluk, was listed in 1850/51. year. Thus, we obtained very important data for this turbulent period in the area of ​​Kosovska Mitrovica and its surroundings.
Keywords: Key words: Bugariće, Srbovac, nahija Mitrovica, Ottoman empire, Cen